Teores de elementos potencialmente tóxicos em solo com adição de cama de aviário e calcário - Mello, Débora de (2021)
The broiler production chain is one of the most expressive in Brazilian agribusiness. The Southwest region of Paraná is the second largest producer of chicken meat in the state. Thus, there is an increasing production of organic waste in the form of poultry litter, from the confinement and handling of birds. Thus, poultry litter becomes an alternative source of fertilization for agriculture, in addition to the limestone used to correct acidity problems, but indiscriminate use can mineralize potentially toxic elements (EPT) and this can affect soils, courses of 'water, and crops. In this sense, the general objective of this research was to quantify the contents of As, Ni, Cd, Cr, Cu and Zn, in an oxisol in the experimental area of UTFPR campus Pato Branco, under an experiment that had been going on for 8 years. The years analyzed in this work were outside 2017 and 2018 where the crops were oat/corn. The soil only had limestone addition in 2015 and aviary bedding was added once a year. The specific objectives were to evaluate the mobility of the elements, As, Ni, Cd, Cr, Cu, and Zn through the quantitative characterization of soils collected in the layers, 0 - 10, 10 - 20, 20 - 40 and 40 - 60 cm; Compare the contents of As, Ni, Cd, Cr, Cu and Zn, for the soils under the addition of 0, 4, 8 and 12 t ha-1 of poultry litter; To analyze the effect of four doses of limestone (0, 2, 4 and 8 t ha-1) on the contents and behavior of potentially toxic elements in the soil; Relate the contents of potentially toxic elements in different soil depths as a function of lime and litter doses through a multivariate analysis; To propose a simple, fast and low-cost methodology for the digestion of soil and litter samples for the quantification of the elements As, Ni, Cd, Cr, Cu and Zn in an inductively coupled plasma optical emission spectrometer (ICP-OES) . The EPT digestion method used was considered efficient in relation to recovery rates, in addition to being safe, easy reproducibility and adaptation, fast and cheap. Regarding the mobility of the elements in the soil profile, it can be concluded that the element As is found in layers below 20 cm due to competition with organic matter and phosphorus and had an increase with the dosages poultry litter of 8 t.ha-1. The elements Cd and Cr have facilitated mobility at pH below 6.0 and decreased as the poultry litter dosage increased. The elements Cu and Zn have an increase in the fertilized soil due to their intensive use of poultry feed. Cu accumulates below 40 cm of the soil due to the lower accumulation of roots and the long periods of fertilization. Zn accumulates in the first layers and is increased with dosages of 4 and 12 t ha-1 of poultry litter. The effect of liming the soil showed little influence on the behavior of the elements, as it was applied only once eight years ago. Although the poultry litter added to the soil for 8 years provides an increase in the levels of EPT in the soil, these presented levels below the values established by the CONAMA no 420, but it is always necessary to monitor and analyze these elements in the soil annually.